Protective effect of royal jelly on fluoride-induced nephrotoxicity in rats via the some protein biomarkers signalling pathways: a new approach for kidney damage. (14th October 2022) - Aslan, Abdullah; Beyaz, Seda; Gok, Ozlem; Can, Muhammed Ismail; Parlak, Gozde; Gundogdu, Ramazan; Ozercan, Ibrahim Hanifi; Baspinar, Serpil
Abstract: Introduction: Protective effect of royal jelly (RJ) on fluoride-induced nephrotoxicity was investigated in this study. Methods: 42 healthy male Wistar rats (n = 42, 8 weeks of age) were divided equally into 6 groups with 7 rats in each; (1) Group-1: Controls fed with standard diet; (2) Group-2: RJ [100 mg/kg] bw (body weight), by oral gavage; (3) Group-3: Fluoride [50 mg/kg] bw, in drinking water; (4) Group-4: Fluoride [100 mg/kg] bw, in drinking water; (5) Group-5: RJ [100 mg/kg] bw, by oral gavage + Fluoride [50 mg/kg] bw, in drinking water; (6) Group-6: RJ [100 mg/kg] bw, by oral gavage + Fluoride [100 mg/kg] bw, in drinking water. After 8 weeks, all rats were decapitated and their kidney tissues were removed for further analysis. The protein expression levels of caspase-3, caspase-6, caspase-9, Bcl-2, Bax, VEGF, GSK-3, BDNF, COX-2 and TNF-α proteins in kidney tissue were analysed by western blotting technique Results: RJ increased Bcl-2, COX-2, GSK-3, TNF-α and VEGF protein levels and a decreased caspase-3, caspase −6, caspase-9, Bax and BDNF protein levels in fluoride-treated rats. Conclusion: RJ application may have a promising therapeutical potential in the treatment of many diseases in the future by reducing kidney damage.